2007
DOI: 10.1063/1.2775038
|View full text |Cite
|
Sign up to set email alerts
|

Dresselhaus effect in bulk wurtzite materials

Abstract: The spin-splitting energies of the conduction band for ideal wurtzite materials are calculated within the nearest-neighbor tight-binding method. It is found that ideal wurtzite bulk inversion asymmetry yields not only a spin-degenerate line ͑along the k z axis͒ but also a minimum-spin-splitting surface, which can be regarded as a spin-degenerate surface in the form of bk z 2 − k ʈ 2 =0 ͑b Ϸ 4͒ near the ⌫ point. This phenomenon is referred to as the Dresselhaus effect ͑defined as the cubic-ink term͒ in bulk wur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…I Q can be written as I Q,s 1 ,s 2 = s 1 |e iQ·r |s 2 = δ σ 1 ,σ 2 F (m 1 , m 2 , q y , a y )F (n 1 , n 2 , q x , a x ), with F (m 1 , m 2 , q, a) being expressed as Eq. (248). For small spin polarization, the contribution from the Hartree-Fock term in the coherent term is negligible [41,42,44] and the spin precession is determined by the spin-orbit coupling,ρ h…”
Section: Hole Spin Relaxation In P-type (001) Gaas Quantum Wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…I Q can be written as I Q,s 1 ,s 2 = s 1 |e iQ·r |s 2 = δ σ 1 ,σ 2 F (m 1 , m 2 , q y , a y )F (n 1 , n 2 , q x , a x ), with F (m 1 , m 2 , q, a) being expressed as Eq. (248). For small spin polarization, the contribution from the Hartree-Fock term in the coherent term is negligible [41,42,44] and the spin precession is determined by the spin-orbit coupling,ρ h…”
Section: Hole Spin Relaxation In P-type (001) Gaas Quantum Wiresmentioning
confidence: 99%
“…10 In contrast to the zincblende semiconductors such as GaAs, the existence of hexagonal c-axis in wurtzite semiconductors leads to an intrinsic wurtzite structure inversion asymmetry in addition to the bulk inversion asymmetry [246,247]. Therefore, the electron spin splittings include both the Dresselhaus effect [245,248] (cubic in k) and Rashba effect (linear in k) [124,125,[249][250][251][252][253][254]. In a recent work by Fu and Wu [245], a Kane-type Hamiltonian was constructed and the spin-orbit coupling for electron and hole bands were investigated in the full Brillouin zone in bulk ZnO and GaN.…”
Section: Spin-orbit Coupling In Wurtzite Semiconductors and Other Matmentioning
confidence: 99%
“…10,26,28 The parameter b is roughly equal to four for all wurtzite materials. 28 Note that there is no spin splitting along the hexagonal axis ͑z͒.…”
Section: Dp Mechanism In Wurtzite Crystal Structuresmentioning
confidence: 99%
“…where m * is the electron effective mass in the absence of electronphonon and SO couplings, p x and p y are the electron momentum operators, V z c ( ) is a nanoscale confinement potential, which confines the electrons only along the z direction, R α is the Rashba [45] and D γ and b 4.28 = Dresselhaus SO coupling parameters [46], [48], x σ and y σ are Pauli spin matrices. The well-known solution of eigenvalue problem of Hamiltonian H el can be given as [38]:…”
Section: Theorymentioning
confidence: 99%
“…Particularly, it is shown, that in bulk wurtzite structures, there are two wurtzite bulk inversion asymmetry effects; Dresselhaus effect which leads to a k 3 term and the wurtzite structure inversion asymmetry effect (which may be called as the Rashba effect) in bulk wurtzite which yields a linear-k term in the two-band kÁ p model [19,44]. The spin-splitting energies of the conduction band for ideal wurtzite materials are calculated [45] within the nearest-neighbor tight-binding method. It is found that ideal wurtzite bulk inversion asymmetry yields not only a spin-degenerate line but also a minimum-spin-splitting surface, which can be regarded as a spin-degenerate surface.…”
Section: Introductionmentioning
confidence: 99%